Produção de hidrogênio e etanol em reator anaeróbio de leito fluidizado: avaliação do desempenho de três materiais suporte em diferentes condições operacionais - Barros, Aruana Rocha (2012)
Hydrogen and ethanol production using microorganisms is a promising area of technological development from a wide variety of renewable and alternative to this production is the use of anaerobic fluidized bed reactor (AFBR). One of the factors that most influence the performance of the AFBR is the material support, which must provide abrasion resistance, porous surface conducive to colonization by microorganisms, easy to achieve fluidization and ability to promote mass transfer between the medium and biofilm. Thus, the objective of this study was to evaluate the influence of different support materials (polystyrene - R1, grounded tire - R2 and polyethylene terephthalate (PET) - R3) on producing hydrogen and ethanol using three anaerobic fluidized bed reactors. Each reactor had a total volume of 4192 cm3 and was fed with media containing glucose as the carbon source (4000 mg L-1) with an influent pH around 5.0 and an effluent pH of about 3.5, a hydraulic retention time (HRT) of 8 1 h at a temperature of 23 2 ºC, with thermal treatment of the inoculum. For hydrogen production, the best performance was achieved with R2 (2.11 mol H2 mol-1 glucose), providing the highest H2 content in biogas (60%). In all reactors, the predominant soluble metabolites were acetic acid, butyric acid, lactic acid and ethanol, with small amounts of propionic acid. The reactor R2 produced more acetic and butyric acid (434.74 and 1013.61 mg L-1, respectively). However, reactor R3 showed a better performance for ethanol production (1941.78 mg L-1).